Lilian’s dilemma: sexuality in professional performance in psychology - Silva, Matheus Estevão Ferreira da [UNESP] (Springer Nature, 2024)
This dilemma is directed to adults and youth attending high school in the area of Psychology. It refers to a situation in which a clinical psychologist, who provides therapeutic services to an adolescent, is faced with the dilemma in which she must choose whether or not to break professional confidentiality, because the adolescent’s family is demanding that she reveals confidential information addressed in therapy regarding his sexuality, under threat of removing him from therapy. The values of patient integrity/dignity and trust are at stake. Audience: Adults and teenagers (high school and above) Field: Psychology.